Pengaruh Risiko Litigasi, Ukuran KAP dan Leverage Terhadap Konservatisme Akuntansi (Studi Kasus Pada Perusahaan Sektor Energi) - Gibran Hadri Ramadan; Sutoyo Sutoyo (Politeknik Ganesha Medan, 2026)
This study examines the effect of litigation risk, the size of public accounting firms, and leverage on accounting conservatism in energy sector companies listed on the Indonesia Stock Exchange (IDX) during the period 2020–2024. The energy sector has unique characteristics, such as high regulatory pressure, environmental risk, and long-term financing complexity, which make the application of conservative accounting especially relevant. Accounting conservatism is used as a prudential mechanism to mitigate information asymmetry, legal exposure, debt covenant violations, and agency conflicts. This study employs a quantitative approach using secondary data from annual and sustainability reports, with a total of 275 firm-year observations selected through purposive sampling. Panel data regression using the Fixed Effect Model (FEM) was applied after conducting model selection tests. The results show that litigation risk and leverage have a positive and significant effect on accounting conservatism, indicating that companies facing high legal exposure and debt obligations tend to adopt more conservative reporting practices. Conversely, the size of public accounting firms does not significantly influence accounting conservatism, suggesting that conservatism in the energy sector is more driven by regulatory and contractual pressures than by auditor reputation.